1994
DOI: 10.1126/science.7521541
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nitric Oxide in the Elimination of a Transient Retinotectal Projection in Development

Abstract: The adult pattern of axonal connections from the eye to the brain arises during development through the refinement of a roughly ordered set of connections. In the chick visual system, refinement normally results in the loss of the ipsilateral retinotectal connections. Inhibition of nitric oxide synthesis reduced the loss of these transient connections. Because nitric oxide is expressed by tectal cells with which retinal axons connect and because reduction of nitric oxide synthesis by tectal cells resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(154 citation statements)
references
References 48 publications
6
146
1
1
Order By: Relevance
“…Because blockade of NOS at early ages does not interfere with the formation of eye-specific layers, it is unlikely that NO produced in the neuropil is involved in early retinogeniculate pattern formation. A developmental role for NO has also been found in the chick retinotectal pathway, where NOS expression is highest during the removal of a transient ipsilateral projection and blockade of NOS results in the retention of this projection (Wu et al, 1994). NO is thus required for the refinement of eye-specific projections from the retina to the optic tectum in the chick.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because blockade of NOS at early ages does not interfere with the formation of eye-specific layers, it is unlikely that NO produced in the neuropil is involved in early retinogeniculate pattern formation. A developmental role for NO has also been found in the chick retinotectal pathway, where NOS expression is highest during the removal of a transient ipsilateral projection and blockade of NOS results in the retention of this projection (Wu et al, 1994). NO is thus required for the refinement of eye-specific projections from the retina to the optic tectum in the chick.…”
Section: Discussionmentioning
confidence: 94%
“…Nitric oxide (NO) has been proposed as a diffusible retrograde messenger in the maintenance of hippocampal long-term potentiation (LTP) (Bohme et al, 1991;O'Dell et al, 1991;Schuman and Madison, 1991;Haley et al, 1992;cf. Gribkoff and Lum-Ragan, 1992) and, by analogy, in activity-dependent refinement of connections in the visual pathway during development (Montague et al, 1991;Wu et al, 1994;.…”
Section: Abstract: Diffusible Messenger; Visual System; Lateral Genimentioning
confidence: 99%
“…Mechanisms of this kind may be involved in the regulation of motility of radial glial cells during development, as described in the optic tectum of Xenopus tadpoles [69] In this model, in vivo observations demonstrated that extension and retraction of filopodial processes from radial glia was modulated by visual stimulation through NO signaling downstream NMDA receptor activation [69]. These interactions may be at the basis of the role ascribed to NO in the refinement of retino-tectal and retino-geniculate projections [70-72] and in the regulation of the wiring of the insect nervous system [73]. NO-mediated interactions are not restricted to mechanisms of axon migration and wiring, but they are also involved in developmental migration of neuroblasts and neuronal precursors [74-76].…”
Section: Nitric Oxide-mediated Metabolic and Functional Interactions mentioning
confidence: 99%
“…NO appears to be involved in the removal of transient retinotectal projections, since the blockade of NOS activity results in the maintenance of such connections [47]. Cramer et al reported that NADPH-d activity reaches a peak at about the fourth postnatal week, and then declines by the sixth postnatal week [48], and suggested that this transient expression of NADPH-d may be involved in the development of mature connections within the ferret lateral geniculate nucleus.…”
Section: Posterior Pituitarymentioning
confidence: 99%